Building a new Germany : denazification and political re-education, 1944-1948. - National Archives (Great Britain) (East Ardsley, Wakefield, United Kingdom : Microform Academic Publishers, 2023)
Building a New Germany: Denazification and Political Re-education, 1944-1948 comprises almost 10,000 images, drawn from 46 files in the FO 939 series at The National Archives (UK). The collection explores the process of denazification from a number of angles. It surveys the high-level policy decisions that instigated and framed the re-education process. The documents likewise offer examples of the official guidance and instructions that were sent to camp authorities. You will also find descriptions of the course materials used, reflections of lecturers and educators involved in the process, and the views of German POWs. The collection offers fascinating insights into British perspectives on extreme ideologies, as well as into concepts of brainwashing and indoctrination, including strategies on how to reverse them. It also explores a key transitional period when the British tried to reshape Germany from foe to friend.
Date range: 1944-1948.
Keywords: Denazification -- Germany; Germany -- Foreign relations -- Great Britain; Great Britain -- Foreign relations -- Germany